Kegiatan Finger Painting dan Pelepah Pisang dalam Meningkatkan Perkembangan Motorik Halus pada Anak Usia 5-6 Tahun di TK Dharma Wanita Glagahwero Panti Kabupaten Jember - Rahayu, Nurdianing; Dahlan, Mukhtar Zaini; Suwargono, Trio (Education Journal : Journal Educational Research and Development, 2024)
One method that supports children's literacy skills is finger panting activities. In this activity there are several flexibility components including: finger painting, arranging, and coloring. This activity can even improve children's fine motor skills and can also hone imagination and artistic creativity in children. Implementation of finger painting and banana leaf activities in improving the fine motor skills of children aged 5-6 years at Dharma Wanita Glagahwero Panti Kindergarten, Jember Regency, namely: the teacher determines the theme, the teacher prepares the media, the teacher informs the theme that will be used, the teacher informs the media that will be used , the teacher tells the child how to do the assignment, the teacher provides guidance and motivation to the child when doing the assignment, the teacher gives direction to the child to submit the assignment, and finally the teacher carries out an evaluation.